2001
DOI: 10.1007/s12144-001-1010-7
|View full text |Cite
|
Sign up to set email alerts
|

Factor-analytic structures in the English and Japanese versions of the Objective Measure of Ego-Identity Status (OMEIS)

Abstract: This research describes an exploratory factor analysis for the purposes of factorial validation for both the English and Japanese versions of the Objective Measure of Ego-Identity Status (OMEIS)--Ideological version (Adams, Bennion, & Huh, 1989). The Japanese OMEIS is a direct translation of the English OMEIS (Ohnishi, 1998). The study reports the factor structure of the OMEIS--Ideological version in English and Japanese. A principal factor analysis (PFA) with both oblique and orthogonal solutions was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…In contrast, Korean college students’ ego-identity achievement is positively related to wisdom and no relationship is found between moratorium and wisdom. According to Ohnishi et al (2001), moratorium and diffusion is in the same construct, which may lead to such results among American students. As Waterman (1999) claimed, although diffusion is considered the least mature, identity statuses are not on a continuum and diffusion, moratorium, and foreclosure have strengths and weakness, which might also explain the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Korean college students’ ego-identity achievement is positively related to wisdom and no relationship is found between moratorium and wisdom. According to Ohnishi et al (2001), moratorium and diffusion is in the same construct, which may lead to such results among American students. As Waterman (1999) claimed, although diffusion is considered the least mature, identity statuses are not on a continuum and diffusion, moratorium, and foreclosure have strengths and weakness, which might also explain the results.…”
Section: Discussionmentioning
confidence: 99%
“…The domains were assessed with a Likert-type scale (ranging from 1 to 5 with 1 = strongly disagree and 5 = strongly agree ). Because of some challenges, wherein some individuals may reveal more than one identity status and similar constructs between moratorium and diffusion (Ohnishi, Ibrahim, & Owen, 2001), the identity statuses were adopted as latent variables rather than categorizing the participants in each ego-identity status group. Because the ego-identity items include multiple domains and each domain has a small number of items (two), RV-EOM-EIS has low internal consistencies: Cronbach’s alpha greater than .60, except for interpersonal moratorium, which was .58 (Bennion and Adams).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we treat identity status as latent variables rather than analyzing membership. Nonetheless, even with this challenge, RV-EOM-EIS has been widely used because of the quantitative nature of the measure based on Marcia’s ego-identity status theory (Bishop, Weisgram, Holleque, Lund, & Wheeler-Anderson, 2005; Ohnish, Ibrahim, & Owen, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…One of the few studies to pursue a cross-national study of Eastern versus Western identity (Rhee et al 1995) found that Europeans used traits and emotional states more than Koreans to describe themselves, whereas Koreans were more likely to use specific attributes and global descriptions. Ohnishi et al (2001) attempted to compare the factor structure of a North American measure of identity formation (the Objective Measure of Ego-Identity Status; Adams et al 1989) between American and Japanese samples of adult women. They found that the factor structures were not equivalent, and suggested that American concepts of identity development may not be completely relevant to the Japanese context.…”
Section: Eastern Views Of Identitymentioning
confidence: 99%